New Research in Polarimetric SAR Technique for Archaeological Purposes using ALOS PALSAR Data. Issue 2 (21st May 2013) - Dore, Nicole; Patruno, Jolanda; Pottier, Eric; Crespi, Mattia; Lasaponara, Rosa; Masini, Nicola
ABSTRACT The work presented here is a further study of the UNESCO Cultural Heritage sites of Samarra (Iraq) and Djebel Barkal archaeological area (Sudan) by means of polarimetric products of the Japanese satellite ALOS PALSAR. Despite the Iraqi war ending in 2011, the city of Samarra is still included on the UNESCO List of Sites in Danger (since 2007). The study of the city presented here began three years ago with the analysis of optical data. The work showed an urban and agricultural expansion affecting the integrity of the city. An attempt to study Samarra by using the polarimetric SAR technique was made in previous years with the employment of the ALOS PALSAR satellite. That study was limited to the analysis of polarimetric descriptors such as entropy and alpha angle, parameters that gave results regarding prevalence of double‐bounce and volume scattering mechanisms in the area investigated. The second archaeological site, Djebel Barkal, is one of five archaeological sites located in a semi‐desert area along the River Nile, in the Napatan Region considered to be part of Nubia. The site was included in the UNESCO World Heritage List in 2003. Polarimetric descriptors considered in previous studies of the zone were entropy and alpha angle. Also in this case, a deeper analysis was carried out with the addition of a second ALOS PALSAR polarimetric SAR image, acquired 3 years later. In the present work, more polarimetric parameters, such as Freeman and Yamaguchi decompositions, are taken into account in order to observe scattering mechanisms both upon the structures already known and the area around them. Thanks to these decompositions and the archaeological maps that were available, it was possible to validate backscattered responses in ALOS PALSAR images as archaeological structures. Copyright © 2013 John Wiley & Sons, Ltd.